2009
DOI: 10.1007/s10895-009-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

A Fiber-Optic Evanescent Wave O2 Sensor Based on Ru(II)-Doped Fluorinated ORMOSILs

Abstract: A novel fiber-optic evanescent wave sensor (FOEWS) for O(2) detection based on [Ru(bpy)(3)](2+)-doped hybrid fluorinated ORMOSILs (organically modified silicates) has been developed. The sensing element was fabricated by dip-coating the optical fiber with [Ru(bpy)(3)](2+)-doped hybrid fluorinated ORMOSILs composed of n-propyltrimethoxysilane (n-propyl-TriMOS) and 3, 3, 3-trifluoropropyltrimethoxysilane (TFP-TriMOS). Fluorophores of [Ru(bpy)(3)](2+) were excited by the evanescent wave field produced on the fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Recently, several efforts have been made to investigate mesoporous, micro, and nano-based matrix materials to improve the performance [20,21,22,23,24]. It has been indicated that utilizing micro and nano-materials could enhance the performance of ruthenium complex-based sensors; for instance, improving the limit of detection, stability, and emission intensity [10,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several efforts have been made to investigate mesoporous, micro, and nano-based matrix materials to improve the performance [20,21,22,23,24]. It has been indicated that utilizing micro and nano-materials could enhance the performance of ruthenium complex-based sensors; for instance, improving the limit of detection, stability, and emission intensity [10,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…The ruthenium complexes were intensively used in silicone [3], sol-gel [26][27][28][29][30], ORMOSILs (organically modified silicates) or in modified ORMOSILs [12,31,32]. A detailed comparison of the performances of such optical oxygen sensors in terms of matrix materials, sensitivity, working range and detection limit has been reported earlier [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ORMOSILs-coated probe showed several strong peaks due to existing 3,3,3-trifluoropropyltrimethoxysilicane (TFP-TriMOS) and n-propyltrimethoxysilane (n-propyl-TriMOS) and reaction with surface hydroxyl Si-OH of the fiber optic probe. Except for the peaks for asymmetric and symmetric stretching vibration of Si-O-Si bond, 3,442 cm −1 , 2,980 cm −1 , and 1,635 cm −1 correspond to physical absorption of water, stretching vibration of C-H bond, and surface hydroxyl of Si-OH, respectively, several other groups of strong peaks are also shown20. For example, 1,450, 1,375, and 1,317 cm −1 were corresponding to rocking vibration, wagging vibration, and twisting vibration of C-H for CH 2 , respectively; 1,269 and 1,220 cm −1 correspond to asymmetric and symmetric stretching vibration of C-F bond, respectively; and 901 and 838 cm −1 correspond to vibration of Si-C bond1920.…”
Section: Resultsmentioning
confidence: 99%
“…Except for the peaks for asymmetric and symmetric stretching vibration of Si-O-Si bond, 3,442 cm −1 , 2,980 cm −1 , and 1,635 cm −1 correspond to physical absorption of water, stretching vibration of C-H bond, and surface hydroxyl of Si-OH, respectively, several other groups of strong peaks are also shown20. For example, 1,450, 1,375, and 1,317 cm −1 were corresponding to rocking vibration, wagging vibration, and twisting vibration of C-H for CH 2 , respectively; 1,269 and 1,220 cm −1 correspond to asymmetric and symmetric stretching vibration of C-F bond, respectively; and 901 and 838 cm −1 correspond to vibration of Si-C bond1920. These results indicate that the ORMOSIL-based film has been successfully modified onto the surface of the fiber optic probe.…”
Section: Resultsmentioning
confidence: 99%